(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
As we know by naturehuman beings are competitive and aspire for excellence in every given field.Not only individuals but nations also want to slow their supremacy in the fieldof sports. This friendly rivalry has inspired and motivated all to sweat andstrive in the competition arena. Training in game and sports is no longer amyth and it has no casual approach but it provides opportunities for scientificprocess and verification.